Epidemiologic aspects of fatal motor vehicle traffic accidents in the city of Salvador, Brazil - Pugliese, Celso; Carvalho, Fernando; Bião, Dulce; Dias, Celia Guimarães Netto (Revista de Saúde Pública, 1975)
A study was made aiming at the description of epidemiologic aspects of fatal motor vehicle accidents in the City of Salvador, Brazil. The study involved the collecting of data in both the Traffic Department (DETRAN) and the Legal Medicine Institute. The study showed a time relationship, i.e., the highest percentage of accidents due to motor vehicles was concentrated at noon and during weekends. Young male drivers were more frequently involved in accidents than females of the same age. The authors indicated that pedestrian fatal accidents are essencially an urban problem needing a great deal of concern by educators and providers of public services. They also suggested the necessity of improving and of homogenizing the notification and classification system of motor vehicle accidents by the DETRAN in Salvador.